The Burden and Cost of Diabetes Amongst Latin Minorities in California - Villanueva, Gennesis Amador; O’Lawrence, Henry; Martinez, Linda (British Journal of Healthcare and Medical Research, 2025)
Diabetes disproportionately impacts older people generally, while Hispanics are almost twice as likely as non-Hispanic whites (nHWs) to be diagnosed. Racial and ethnic disparities exist and influence the burden and cost of diabetes care for Medicare recipients among Hispanics. The current annual global costs estimated to be U.S. 673 billion, and these are projected to rise to U.S. 802 billion by 2040 and diabetes care accounts for one of every dollar spent on health care. It can be said that old age and diabetes place a disproportionate burden on racial and ethnic minorities compared with non-Hispanic whites (nHWs), Hispanics (who comprise 18% of the U.S. population are almost twice as likely to develop type 2 diabetes (T2D) as nHWs) and experience high rates of poorly controlled diabetes and related complications [1]. This research aims to influence policy decisions at multiple levels. Policymakers can utilize the insights gained to advocate for targeted interventions that improve diabetes management and reduce healthcare costs among Latinx minorities in California.